Genome-resolved analyses of oligotrophic groundwater microbial communities along phenol pollution in a continuous-flow biodegradation model system - Yavari-Bafghi, Maryam; Rezaei Somee, Maryam; Amoozegar, Mohammad Ali; Dastgheib, Seyed Mohammad Mehdi; Shavandi, Mahmoud (Frontiers in Microbiology, 2023)
Groundwater pollution is one of the major environmental concerns. The entrance of pollutants into the oligotrophic groundwater ecosystems alters native microbial community structure and metabolism. This study investigated the application of innovative Small Bioreactor Chambers and CaO2 nanoparticles for phenol removal within continuous-flow sand-packed columns for six months. Scanning electron microscopy and confocal laser scanning microscopy analysis were conducted to indicate the impact of attached biofilm on sand surfaces in bioremediation columns. Then, the influence of each method on the microbial biodiversity of the column’s groundwater was investigated by next-generation sequencing of the 16S rRNA gene. The results indicated that the simultaneous application of biostimulation and bioaugmentation completely eliminated phenol during the first 42 days. However, 80.2 % of phenol remained in the natural bioremediation column at the end of the experiment. Microbial diversity was decreased by CaO2 injection while phenol-degrading orders such as Rhodobacterales and Xanthomonadales were dominated in biostimulation columns. Genome-resolved comparative analyses of oligotrophic groundwater prokaryotic communities revealed that Burkholderiales, Micrococcales and Cytophagales were the dominant members of the pristine groundwater. Six-month exposure of groundwater to phenol shifted the microbial population towards increasing the heterotrophic members of Desulfobacterales, Pseudomonadales and Xanthomonadales with the degradation potential of phenol and other hydrocarbons.